Delivering Flexible Education and Training to Health Professionals: Caring for Older Adults in Disasters. (25th April 2016) - Altman, Brian A.; Gulley, Kelly H.; Rossi, Carlo; Strauss-Riggs, Kandra; Schor, Kenneth
Abstract: The National Center for Disaster Medicine and Public Health (NCDMPH), in collaboration with over 20 subject matter experts, created a competency-based curriculum titled Caring for Older Adults in Disasters: A Curriculum for Health Professionals . Educators and trainers of health professionals are the target audience for this curriculum. The curriculum was designed to provide breadth of content yet flexibility for trainers to tailor lessons, or select particular lessons, for the needs of their learners and organizations. The curriculum covers conditions present in the older adult population that may affect their disaster preparedness, response, and recovery; issues related to specific types of disasters; considerations for the care of older adults throughout the disaster cycle; topics related to specific settings in which older adults receive care; and ethical and legal considerations. An excerpt of the final capstone lesson is included. These capstone activities can be used in conjunction with the curriculum or as part of stand-alone preparedness training. This article describes the development process, elements of each lesson, the content covered, and options for use of the curriculum in education and training for health professionals. The curriculum is freely available online at the NCDMPH website athttp://ncdmph.usuhs.edu ( Disaster Med Public Health Preparedness . 2016;10:633–637).